Pendampingan Penguatan Kapasitas Keterampilan Penulisan Karya Ilmiah bagi Mahasiswa Santri di Pondok Pesantren Mahasiswa Universal - Wahyudin Darmalaksana; Tatang Astarudin; Dhita Fadhilatul Azizah; Devi Rizki Apriliani (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss strengthening the skills of writing scientific papers in student boarding schools. This study used a qualitative approach with a descriptive-analytical method. The results of the research and discussion show that kiyai leadership, scientific publication best practices, training and mentoring can play an effective role for student boarding schools and even to leverage the productivity of scientific publications. This research concludes that training and mentoring are relevant to the agenda of strengthening students' skills in writing scientific articles in student boarding schools.